2011
DOI: 10.1108/13552541111098626
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary design and manufacturing study of hybrid lightweight high‐speed wind‐tunnel models

Abstract: PurposeIn view of the strength and stiffness deficiencies of current photopolymer resin models under high aerodynamic loads, the purpose of this paper is to introduce a preliminary design and manufacturing technique for hybrid lightweight high‐speed wind‐tunnel models with internal metal frame and surface photopolymer resin based on rapid prototyping (RP).Design/methodology/approachInternal metal frame structure was designed to be of regular configurations that can be conveniently fabricated by conventionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In order to improve the structural integrity of RP models and reduce the manufacturing period and cost, in Refs. [278] and [279], a preliminary design and manufacturing technique is introduced. This technique is applied to hybrid high-speed wind-tunnel models with an internal frame and an outer resin, fabricated, respectively, with a conventional method and stereolithography.…”
Section: Rapidmentioning
confidence: 99%
“…In order to improve the structural integrity of RP models and reduce the manufacturing period and cost, in Refs. [278] and [279], a preliminary design and manufacturing technique is introduced. This technique is applied to hybrid high-speed wind-tunnel models with an internal frame and an outer resin, fabricated, respectively, with a conventional method and stereolithography.…”
Section: Rapidmentioning
confidence: 99%
“…In contrast, the FDM model with chromium coating had accurate results comparable to the conventional steel model. Yang et al [14] reinforced the photopolymer resin material with an internal metallic structure to reduce the weight and avoid the resonance phenomenon. They reported that the RP models suffered from deformation at a higher speed, particularly the thin regions such as the wing tip, which resulted in variations in the wind tunnel results.…”
Section: Introductionmentioning
confidence: 99%
“…Standard models are also used to provide baselines for correlation of results from different wind tunnels [1][2][3], to check data repeatability over time [4], for checkouts of wind tunnel systems after repairs or modifications, for the assessment of wall interference effects [5,6], for verification of new measurement techniques or devices [7], for the validation of new model manufacturing technologies [8][9][10], for training of wind tunnel personnel [11]. Besides, results from wind tunnel tests of standard models are used as test cases for the verification of computational-fluiddynamics (CFD) computer codes [12].…”
Section: Introductionmentioning
confidence: 99%